Organic animal husbandry: concept, status and possibilities in India-A review - Chander, Mahesh; Mukherjee, Reena (The Indian Journal of Animal Sciences, 2005)
The animal production system, may be broadly classified as traditional, conventional and organic with their distinct characteristics.While traditional and conventional production systems are well established and their respective features known widely, the organic animal husbandry system has emerged only recently, which is still evolving. Many believe that the organin animal husbandv is same as traditional animal husbandry practiced in India since centuries, which of course, it is not. The organic animal husbandry is far more sophisticated and knowledge intensive system of' animal production meant to safeguard not only the human health but also the welfare of animals and the environment on the whole. Thus, it is important to develop correct understanding of the organic farming and especially the organic animal husbandry per se. This review therefore has attempted not only to define the organic farming and organic animal husbandry production system and progress made around the world in this front, but also explored the oppurtunities for India in this regard.